2020
DOI: 10.1101/2020.06.17.20133611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Fear of COVID-19 during the Rapid Rise Period in Bangladesh

Abstract: Objectives: To determine the level of Knowledge, Attitude, and Practice (KAP) related to COVID-19 preventive health habits and perception of Fear towards COVID-19 in subjects living in Bangladesh. Design: Prospective, cross-sectional survey of (n= 2157) male and female subjects, 13-90 years of age, living in Bangladesh. Methods: Ethical Approval and Trial registration were obtained prior to the commencement of the study. Subjects who volunteered to participate and signed the informed consent were enrolled i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
34
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 14 publications
13
34
0
Order By: Relevance
“…This finding is supported by other studies 18 , 27 though many studies had a vice-versa result 2 , 5 , 15 , 19 , 27 , 28 . In this study, the participants aged 50 years and above had a higher knowledge score at the bivariable level, similar to other studies 5 , 7 , 15 , 19 , 27 , 28 , 29 , 30 , 31 . However, we dropped the age variable from the multiple regression analysis due to its multicollinearity with education and marital status.…”
Section: Discussionsupporting
confidence: 85%
“…This finding is supported by other studies 18 , 27 though many studies had a vice-versa result 2 , 5 , 15 , 19 , 27 , 28 . In this study, the participants aged 50 years and above had a higher knowledge score at the bivariable level, similar to other studies 5 , 7 , 15 , 19 , 27 , 28 , 29 , 30 , 31 . However, we dropped the age variable from the multiple regression analysis due to its multicollinearity with education and marital status.…”
Section: Discussionsupporting
confidence: 85%
“…Also, the present study showed that there was a statistically significant strong negative correlation between fear from COVID-19 and either total Knowledge about COVID-19 scores & total COVID-19 preventive practices scores in both middle aged and older adults groups. It was in the same line with Hossain et al, [31] who reported that knowledge scores showed contrasting correlation with Fear scores. In contrast, Ali et al, [5] didn't find a correlation between fear and knowledge.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the relation between residence and fear from COVID-19 among the studied subjects, the current study revealed that study subjects who were living in rural areas had a higher level of COVID-19 fear than those who were living in urban areas. Otherwise, a study was done in Bangladesh by Hossain et al, [31] revealed that Dhaka urban dwellers reported a higher status of COVID-19 fear than rural dwellers this may due to subjects in a rural area had fewer health centers and had difficult to access health centers than who residing in urban, so they fear from acquiring disease than others. Also, the present study showed that there was a statistically significant strong negative correlation between fear from COVID-19 and either total Knowledge about COVID-19 scores & total COVID-19 preventive practices scores in both middle aged and older adults groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving Israeli subjects, and applying a modified version of the Fear of COVID-19 scale (FCV-19S; Ahorsu et al., 2020 ), five factors (gender, sociodemographic status, chronic illness, being in an at-risk group, and having a family member dying of COVID-19) were shown to be associated with fear of COVID-19 ( Tzur Bitan et al., 2020 ). In Bangladesh, despite that fear, respondents were mostly positive, indicating that they believed the disease was “controllable and containable” ( Hossain et al., 2020 ). In a small sample of Americans, depending on the “dark” personality trait (narcissism, Machiavellianism, psychopathy, and sadism), COVID-19 was perceived either as a threat of instability or as a positive protective measure ( Hardin et al., 2020 ).…”
Section: Coronex: Possible Primary and Secondary Influencing Or Inducmentioning
confidence: 99%